The Contribution of Muslim Scholars and Islamic Social Organizations in Developing Ḥadith Studies in Indonesia - Masruhan, Masruhan; Hasyim, Muh. Fathoni (Universitas Islam Negeri Mataram, 2024)
Hadith studies in Indonesia have lagged despite hadith being the second source of Islam. The question is how Muslim scholars and Islamic social organizations have contributed to developing hadith studies in Indonesia. To answer this, library research with an analytical approach was conducted to discover a description of their contributions. Data was gathered through a literature study, analyzing references written by Muslim scholars in Indonesia using inductive and content analysis. The result shows that the lag in hadith studies is due to the lack of attention from Muslim scholars and the limited resources of hadith. However, Hadith studies began to be experienced in the second half of the 19th Century, growing to the early 20th Century. This was, among others, driven by the purification of Islamic teachings and the critique of Orientalists who undermined hadith. In this context, Muslim scholars and Islamic social organizations in Indonesia have significantly contributed to the development of hadith studies, mainly through providing literature on hadith and its sciences. However, their approaches differ. Muslim scholars interpret hadith textually and contextually, while Islamic social organizations, except NU, primarily use a textual approach. NU, in contrast, applies both approaches in its deliberations.